MENELISIK PERAN PERSEPSI KONSUMEN MELALUI MINAT BELI: PROMOSI PRODUK RICHEESE FACTORY - Ahmad Farih Awwalunnajjah; Roymon Panjaitan; Diana Aqmala; Handy Nur Cahya (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This research investigates how the characteristics of virtual influencers influence consumers’ purchase intention, with consumer perception acting as a mediating variable. A quantitative explanatory method was applied, involving 134 social media users who had been exposed to promotional content by the virtual influencer Arbie Seo for Richeese Factory. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that credibility and authenticity exert a positive influence on purchase intention, whereas attractiveness shows a significant negative effect. In addition, credibility, attractiveness, and authenticity positively affect consumer perception. Consumer perception subsequently increases purchase intention and serves as a mediator in the relationship between virtual influencer characteristics and purchase intention.